Herbert Standing correspondence - Standing, Herbert, 1846-1923.
ALS (St. Louis, Mo.; undated) to Thomas F. Glancy regarding Glancy's play.
Actor.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Glancy, Thomas F. -- Correspondence; Drama; Actors